Computational analysis of soft polymer lattices for 3D wound dressing materials / Muhammad Hanif Nadhif ...[et al.] - Nadhif, Muhammad Hanif; Irsyad, Muhammad; Utomo, Muhammad Satrio; Suhaeri, Muhammad; Whulanza, Yudan (Universiti Teknologi MARA, 2021)
One of the wound treatments was negative pressure wound therapy (NPWT), which used wound dressings on the wound bed to ameliorate the wound healing. Unfortunately, most wound dressings were two dimensional (2D), lacking the ability to cover severe wounds with a straightforward procedure. The sheets needed to be stacked following the wound curvature, which might be problematic since improper stacking could hinder the wound healing. Regarding the mentioned problems, our group develop 3D wound dressings, which are made using 3D printers. The wound dressings are made of polycaprolactone (PCL), polyurethane (PU), and polyvinyl alcohol (PVA). As the initial stage, the mechanical integrity of the soft polymers was investigated under uniaxial tensile and uniaxial compressive stress using computational methods. The polymers were defined as 3D lattices following the dimension of existing wound dressings. Based on the simulation results of displacement and von Mises stress, the three polymers are mechanically safe to be used as wound dressing materials.